Song Preference in Female and Juvenile Songbirds: Proximate and Ultimate Questions - Fujii, Tomoko G.; Coulter, Austin; Lawley, Koedi S.; Prather, Jonathan F.; Okanoya, Kazuo (Frontiers in Physiology, 2022)
Birdsong has long been a subject of extensive research in the fields of ethology as well as neuroscience. Neural and behavioral mechanisms underlying song acquisition and production in male songbirds are particularly well studied, mainly because birdsong shares some important features with human speech such as critical dependence on vocal learning. However, birdsong, like human speech, primarily functions as communication signals. The mechanisms of song perception and recognition should also be investigated to attain a deeper understanding of the nature of complex vocal signals. Although relatively less attention has been paid to song receivers compared to signalers, recent studies on female songbirds have begun to reveal the neural basis of song preference. Moreover, there are other studies of song preference in juvenile birds which suggest possible functions of preference in social context including the sensory phase of song learning. Understanding the behavioral and neural mechanisms underlying the formation, maintenance, expression, and alteration of such song preference in birds will potentially give insight into the mechanisms of speech communication in humans. To pursue this line of research, however, it is necessary to understand current methodological challenges in defining and measuring song preference. In addition, consideration of ultimate questions can also be important for laboratory researchers in designing experiments and interpreting results. Here we summarize the current understanding of song preference in female and juvenile songbirds in the context of Tinbergen’s four questions, incorporating results ranging from ethological field research to the latest neuroscience findings. We also discuss problems and remaining questions in this field and suggest some possible solutions and future directions.